The Evaluation of Final Assignment System Using the USE Questionnaire Approach - Purwinarko, Aji; Subagja, Mona; Yanuarto, Alfath (Universitas Negeri Semarang, 2020)
Universitas Negeri Semarang has utilized information system technology to facilitate the assessment of final student assignments. So it is necessary to test this information system to determine user satisfaction and the success of the information system in providing services. One way to test the information system is to analyze the usability aspect, using the Usefulness, Satisfaction, and Ease of use (USE) Questionnaire. Data collection involved 75 respondents from users of the final assignment system. The reliability test results on 30 questions resulted in a Cronbach's alpha value of 0.97, which means that the questionnaire's reliability was excellent. Whereas for Usability measurement, the percentage value of Usefulness is 86.7%, Ease of Use is 84.4%, Ease of learning is 86.6%, and Satisfaction is 83.0%, which shows that the final assignment system is very worthy of being used.